Stable dynamics of pneumococcal carriage over a decade in the pre-PCV era. Issue 37 (3rd September 2019) - Wagner, Bradley G.; Althouse, Benjamin M.; Givon-Lavi, Noga; Hu, Hao; Dagan, Ron
Abstract: Streptococcus pneumoniae (SP) nasopharyngeal carriage studies are important to understand SP circulation prior to implementation of vaccination programs. It is generally not known how stable these carriage rates are over time. Carriage studies were conducted in Southern Israel during a decade preceding Pneumococcal Conjugate Vaccine (PCV) introduction. We estimated total and vaccine-type SP carriage at 6 months of age to be stable at 35% (95% CI: 26, 44) and 19% (95% CI: 15, 24), respectively in Jewish and 70% (95% CI, 62, 77) and 41% (95% CI: 38, 45) in Bedouin populations. The stability of carriage rates in two disparate populations over 10 years suggests a single survey may be sufficient to characterize pneumococcal carriage pre-PCV.